2019 IEEE 60th Annual Symposium on Foundations of Computer Science (FOCS) 2019
DOI: 10.1109/focs.2019.00059
|View full text |Cite
|
Sign up to set email alerts
|

New Notions and Constructions of Sparsification for Graphs and Hypergraphs

Abstract: A sparsifier of a graph G (Benczúr and Karger; Spielman and Teng) is a sparse weighted subgraphG that approximately retains the same cut structure of G. For general graphs, non-trivial sparsification is possible only by using weighted graphs in which different edges have different weights. Even for graphs that admit unweighted sparsifiers (that is, sparsifiers in which all the edge weights are equal to the same scaling factor), there are no known polynomial time algorithms that find such unweighted sparsifiers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(61 citation statements)
references
References 16 publications
3
58
0
Order By: Relevance
“…The reduction procedures discussed above may result in large and dense graphs, thus affecting the efficiency of algorithms applied to the reduced graph. A workaround is to find a smaller and sparser graph whose cut approximates, rather than exactly recovers, the hypergraph cut [3,4,5,12,32]. In [5], a sparsification technique is proposed for hypergraphs with submodular cardinality-based splitting functions.…”
Section: Sparsifying Hypergraph-to-graph Reductionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction procedures discussed above may result in large and dense graphs, thus affecting the efficiency of algorithms applied to the reduced graph. A workaround is to find a smaller and sparser graph whose cut approximates, rather than exactly recovers, the hypergraph cut [3,4,5,12,32]. In [5], a sparsification technique is proposed for hypergraphs with submodular cardinality-based splitting functions.…”
Section: Sparsifying Hypergraph-to-graph Reductionsmentioning
confidence: 99%
“…This may result in large and dense graphs thus affecting the efficiency of algorithms applied to the reduced graph. To tackle this problem, sparsification techniques have been developed which try to approximate the hypergraph cut using a sparse graph with fewer auxiliary vertices [3,4,5,12,32]. A followup paper [5] proposes a sparsification method for approximating hypergraph cuts defined by submodular cardinality-based splitting functions.…”
mentioning
confidence: 99%
“…The cut function of a graph G = (V, E) can be seen as a decomposable submodular function F (S) = e∈E f e , where f e (S) = 1 if and only if e ∩ S = ∅ and e ∩ (V \ S) = ∅. The problem of sparsifying a graph while approximately preserving its cut structure has been extensively studied, (See Ahn et al [2012, 2013, Bansal et al [2019], Benczúr and Karger [2015] and references therein.) The pioneering work of Benczúr and Karger [1996] showed for any graph G with n vertices one can construct a weighted subgraph G in nearly linear time with O(n log n/ 2 ) edges such that the weight of every cut in G is preserved within a multiplicative (1 ± )-factor in G .…”
Section: Related Workmentioning
confidence: 99%
“…Recently, Soma and Yoshida [2019] initiated the study of spectral sparsifiers for hypergraphs and showed that every hypergraph admits an -spectral sparsifier with O(n 3 log n/ 2 ) hyperedges. For the case where the maximum size of a hyperedge is r, Bansal et al [2019] showed that every hypergraph has an -spectral sparsifier of size O(nr 3 log n/ 2 ). Recently, this bound has been improved to O(nr(log n/ ) O( 1) ) and then to O(n(log n/ ) O( 1) ) Kapralov et al [2021b,a].…”
Section: Related Workmentioning
confidence: 99%
“…Cuts in graphs are a fundamental object of study, and play a central role in the study of graph algorithms. Consequently, the problem of sparsifying a graph while approximately preserving its cut structure has been extensively studied (see, for instance, [17,6,18,25,1,2,13,5,3,21,15,4,16], and references therein). A cut-preserving sparsifier not only reduces the space requirement for any computation, but it can also reduce the time complexity of solving many fundamental cut, flow, and matching problems as one can now run the algorithms on the sparsifier which may contain far fewer edges.…”
Section: Introductionmentioning
confidence: 99%